Apartment foreclosure discount in Kuala Lumpur - Wong, W.C.; Ng, P.L.; Lee, J.Y.M.; Daud, M.N. (Taylor & Francis, 2015)
With the exception of anecdotal information which suggests that auctioned or foreclosed properties in Malaysia tend to be sold at a deep discount, no study has thus far attempted to quantify this foreclosure discount. This notion is explored by comparing the listing price of auctioned apartments with comparable non-auctioned apartments located within the same building blocks in Kuala Lumpur during the period 2009-2014. The property auction market is predominately relied upon to dispose of foreclosed properties in Malaysia. It is found that foreclosed apartments are listed at a discount of 33.4% as compared to apartments advertised in the private negotiated market. This discount is attributed to “stigma effect” associated with auctioned properties and the imperfections of the Malaysian auction market such as auctioned properties may not carry a clean title, potential buyers cannot view the properties prior to auction and may not obtain vacant possession of the properties. The “proxy effect” was minimal since the matching strategy adopted would have netted out the differentials in locational and neighbourhood characteristics between auctioned and non-auctioned properties.